Pengaruh Tingkat Pendidikan dan Pemahaman Agama Orang Tua Terhadap Hasil Belajar Pendidikan Agama Islam - Reza Reza; Sulaiman Sulaiman (An-Nuha, 2022)
This study aims to: (1) determine the influence of the level of education of parents of class VIII student at SMP Negeri 12 Padang (2) determine the religious understanding of parents of class VIII students at SMP Negeri 12 Padang (3) determine the learning outcomes of Islamic Religious Education for class VIII students at SMP Negeri 12 Padang (4) to find out the effect of the level of education and religious understanding of parents on the learning outcomes of Islamic Religious Education for class VIII students at SMP Negeri 12 Padang. This type of research is quantitative research using survey research methods. The population in this study were parents and class VIII students at SMP Negeri 12 Padang. The samples in this study were parents and students of grades VIII.4, VIII.5, VIII.6 and VIII.7 totaling 61 respondents. The sampling technique in this study used purposive sampling technique. Data collection techniques in this study used observation, questionnaires (questionnaires), interview and documentation. Data analysis, with education level (X1) and parents’ religious understanding (X2) as independent variables and Islamic Religious Education learning outcomes (Y) as dependent variable. The results of this study indicate that there is an influence of the level of education and religious understanding of parents on the learning outcomes of Islamic Religious Education for grade VIII students at SMP Negeri 12 Padang.